Characterization of the proteins of intracisternal type A and extracellular oncornavirus-like particles produced by MOPC-460 myeloma cells. - Robertson, D L (1979)
The mouse plasmacytoma cell line, MOPC-460, produces both intracisternal and intracytoplasmic A-type particles when grown as a solid tumor. When these cells are grown either as an ascites tumor or in tissue culture, a third type of particle is produced extracellularly. This particle, the "myeloma-associated virus," is closely related to, and probably an alternate form of, the intracisternal A-type particle. The proteins present in these two types of particles were compared by tryptic peptide mapping. Both types of particles were found to contain essentially the same major proteins of 76,000 (p76), 68,000 to 70,000 (p68-70), and 45,000 (p45) daltons, in addition to varying amounts of smaller proteins. The relative proportions of all these proteins varied from preparation to preparation in an unpredictable way. The p45, p68, and p70 proteins all contained sequences found in p76, suggesting precursor-product relationships of p76 leads to p70 leads to p45 for solid tumor A-type particles and p76 leads to p68 leads to p45 for extracellular myeloma-associated virus. In addition, immune precipitation experiments have established that p76 contains at least some of the antigenic determinants characteristic of murine leukemia virus p30. This confirms earlier nucleic acid hybridization studies which indicated a moderate degree of relatedness between MOPC-460 A-type particles and several standard murine leukemia and sarcoma viruses. Taken together, our results provide evidence supporting the concept that MOPC-460 A-type particles may represent aberrant forms of C-type murine viruses.